Inflation differentials in the African economic community - Tersoo David Iorngurum (Charles University in Prague, Institute of Economic Studies (IES), 2025)
This paper examines the determinants of inflation differentials across member states of the African Economic Community (AEC). The results suggest that exchange rate depreciation, GDP per capita growth, price divergence, fiscal deficit, and periods of economic instability all contribute to higher differentials. On the other hand, differentials are not significantly influenced by a country's output gap and the persistence of its differentials. Given that price stability and low differentials are essential for monetary integration and improved welfare in the AEC, this study concludes that policies aimed at exchange rate stabilization, fiscal discipline, and fiscal coordination may be beneficial for member states.
Keywords: E31; F41; 330; Inflation differentials; exchange rate; fiscal deficit; GDP per capita growth; price divergence; economic instability; panel data